Active Power Injection Control for Power Converters Connected to the Grid Through an L Filter. Issue 6 (3rd April 2017) - Sosa, Jose M.; Martinez-Rodriguez, Panfilo R.; Escobar, Gerardo; Vazquez, Gerardo; Valdez-Fernandez, Andres A.
ABSTRACT: This paper presents the design, implementation, and evaluation of a model-based controller for a general scheme of transformerless power converters connected to the grid through an L filter. The proposed controller is aimed at active power injection, and consists of a damping term over the current error in addition to a filter parameter estimation scheme. The latter provides estimates of the filter internal resistance and inductance values. It involves the fundamental and quadrature components of the grid voltage to asymptotically compensate for current harmonic peturbations. As a result, the closed-loop system fulfills the active power injection objective. The proposed controller is tested in an experimental setup and its performance is compared to that of the Proportional-Resonant controller. Experimental results are presented for a single-phase H-bridge inverter; however, the control scheme can be used in several other H-bridge based inverter topologies such as H5 and HERIC.